On pain – Virginia Woolf and the language of poets and patients. Issue 4 (November 2021) - Bantel, Carsten; Sörös, Peter
Influenced by Virginia Woolf pain is traditionally believed to be a private object that defies language. However, our analysis of classical and contemporary works of British and American poets, in addition to our own clinical experiences, leads us to challenge this notion. In accordance with Wittgenstein we instead view pain as a concept and objective experience that should encourage interaction. Reasons why patients and healthcare providers often assume language to be insufficient to grasp the complexity of pain are manifold. Based on neuro-cognitive mechanisms we propose an important contributor might be that patients in pain speak a different language than their pain-free peers and doctors.